FAKTOR PROTEKTIF DAN FAKTOR RISIKO YANG MEMPENGARUHI SELF-ESTEEM PADA REMAJA DENGAN DISLEKSIA - Wijanarko, Cornellius Axel; Engry, Agustina; Prasetyo, Eli (Fakultas Psikologi Universitas Hang Tuah, 2023)
Abstract. Adolescence is a transitional period between childhood and adulthood. During this time, the development of self-esteem is critical as it can have a significant impact on future growth. This phase is not exclusive to adolescents with dyslexia, who tend to have lower self-esteem, which indicates the importance of identifying factors of self-esteem in adolescents with dyslexia. This study aims to identify the protective and risk factors that affect the self-esteem of dyslexic adolescents. The study utilized qualitative methods and employed a case study approach. The research was based on the experiences of two participants who were siblings with dyslexia disorder and came from different family backgrounds. The analytical technique used was inductive thematic analysis. The results showed a number of protective factors such as positive family relationship, positive parenting, personality and self-reflection, good academic performance, academic support, and positive relationship with as it peers, and risk factors such as poor family relationship, negative parenting, poor academic performance, academic difficulties, poor relationship with peers, and negative self-acceptance. The most significant factor impacting adolescents with dyslexia is their family relationships and the parenting models implemented.